Patients with MAC Lung Disease Have a Low Visceral Fat Area and Low Nutrient Intake - Kentaro Wakamatsu; Nobuhiko Nagata; Sanae Maki; Hisamitsu Omori; Hiroyuki Kumazoe; Kayoko Ueno; Yuko Matsunaga; Makiko Hara; Koji Takakura; Nagisa Fukumoto; Nobuhisa Ando; Mami Morishige; et al. (Pulmonary Medicine)
Objective. This study aimed to examine the nutritional status and nutrient intake of patients with MAC lung disease with a focus on visceral fat area. Patients and Methods. Among 116 patients of our hospital with nontuberculous mycobacteriosis who were registered between May 2010 and August 2011, 103 patients with MAC lung disease were included in this study. In all patients, nutritional status and nutrient intake were prospectively examined. Results. Patients were 23 men and 80 women (mean age, 72.3±10.9 years). BMI (kg/m2) at the time of registration was 20.4±2.7 in men and 19.2±2.9 in women. Visceral fat area (cm2) was significantly lower in women (35.7±26.6) than in men (57.5±47.4) (p=0.0111). The comparison with general healthy adults according to age revealed a markedly reduced visceral fat area among patients with MAC lung disease. With respect to nutrient intake, energy adequacy (86.1±15.7%), protein adequacy (82.4±18.2%), lipid adequacy (78.1±21.8%), and carbohydrate adequacy (89.6±19.2%) ratios were all low at the time of registration. BMI was significantly correlated with protein adequacy (p=0.0397) and lipid adequacy (p=0.0214) ratios, while no association was found between visceral fat area and nutrient intake. Conclusion. Patients with MAC lung disease had a low visceral fat area and low nutrient intake.